A forty year kiss : a novel [large type] - Butler, Nickolas (Thorndike Press large print top shelf., 2025)
"Charlie and Vivian parted ways after just four years of marriage. Too many problems, too many struggles. When Charlie returns to Wisconsin forty years later, he's not sure what he'll find. He is sure of one thing-he must try to reconnect with Vivian to pick up the broken pieces of their past. But forty years is a long time. It's forty years of other relationships, forty years of building new lives, and forty years of long-held regrets, mistakes, and painful secrets." --